Toner Surface Additives
Patent Information
- Application Number
- JP2021153760
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-09-24
- Filing Date
- 2021-09-22
- Publication Date
- 2025-03-05
- Estimated Expiration
- 2041-09-22
Smart Images

Figure 0007640425000001 
Figure 0007640425000002 
Figure 0007640425000003
Abstract
Description
[Technical field]
[0001] SUMMARY The present disclosure, in various embodiments, relates to toners for use in electrostatographic machines. [Background technology]
[0002] The European Commission has adopted the 14th adaptation to technical progress (ATP) of the CLP Regulation, which includes the 2 The new requirements for titanium dioxide products to carry a cancer warning on the label apply to mixtures in powder form containing 1% or more of material with an aerodynamic diameter of 10 µm or less.
[0003] TiO in toner formulations providing comparable performance 2 Non-carcinogenic alternatives are desirable. Summary of the Invention
[0004] According to various embodiments, a toner composition is provided. The toner composition includes toner particles including a resin, a colorant, and a surface additive applied to the surface of the toner particles. The surface additive is strontium titanate (SrTiO 3 ), silica (SiO 2 ), silicon tetrachloride (SiCl 4 ) and charge control agents.
[0005] A further aspect described herein is a developer. The developer includes a toner composition including toner particles, a colorant, and a surface additive applied to the surface of the toner particles. The surface additive is strontium titanate (SrTiO 3 ), silica (SiO 2 ), silicon tetrachloride (SiCl 4 ) and a charge control agent. The developer comprises a toner carrier.
[0006] A further aspect described herein is a toner composition. The toner composition includes toner particles including a resin and a surface additive applied to the surface of the toner particles. The surface additive is strontium titanate (SrTiO 3 ), silica (SiO 2 ), silicon tetrachloride (SiCl 4 ) and charge control agents. [Brief description of the drawings]
[0007] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate several embodiments of the present teachings and, together with the description, serve to explain the principles of the present teachings.
[0008] [Figure 1] FIG. 1 is a graphical representation of triboelectric charging for various toners under various humidity conditions.
[0009] [Diagram 2] FIG. 2 is a graphical representation of triboelectric charging for various toners at various humidity conditions.
[0010] [Figure 3A] FIG. 3A shows the charging spectrum results for the control toner blend.
[0011] [Figure 3B] FIG. 3B shows the charging spectrum of a 0.65 parts per hundred (pph) toner formulation of SiO2 / SiCl4 / processed SrTiO3.
[0012] [Figure 3C] FIG. 3C shows the charging spectrum of a 1.1 pph toner formulation of SiO2 / SiCl4 / treated SrTiO3.
[0013] It should be noted that some details of these figures have been simplified and are drawn to facilitate understanding of the embodiments without maintaining precise structural accuracy, detail, and / or scale. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] In the following description, reference is made to chemical formulas which form a part hereof and which illustrate certain exemplary embodiments in which the present teachings may be practiced. These embodiments are described in sufficient detail to enable those skilled in the art to practice the present teachings, with the understanding that other embodiments may be utilized and changes may be made without departing from the scope of the present teachings. Thus, the following description is merely illustrative and non-limiting.
[0015] While the numerical ranges and parameters setting forth the broad scope of the present disclosure are approximations, the numerical values set forth in the specific examples are reported as precisely as possible. However, any numerical value inherently contains certain errors necessarily resulting from the standard deviation found in their respective testing measurements. Moreover, all ranges disclosed herein should be understood to encompass any subranges subsumed therein. For example, a range "less than 10" can include any and all subranges between a minimum value of zero and a maximum value of 10 (and inclusive), i.e., any and all subranges having a minimum value equal to or greater than zero and a maximum value equal to or less than 10, e.g., 1 to 5. In certain cases, the numerical values set forth for parameters can assume negative values. In this case, exemplary values of a range set forth as "less than 10" can assume negative values, e.g., -1, -2, -3, -10, -20, -30, etc.
[0016] Although embodiments disclosed herein are not limited in this respect, as used herein, the terms "plurality" and "a plurality" can include, for example, "multiple" or "two or more." The terms "plurality" or "a plurality" may be used throughout this specification to describe two or more components, devices, elements, units, parameters, etc. For example, "multiple resistors" can include two or more resistors.
[0017] The toner can be any suitable or desired toner, including conventional toners prepared by mechanical comminution processes, or chemical toners prepared by chemical processes such as emulsion aggregation and suspension polymerization.
[0018] In this embodiment, titanium dioxide (TiO 2 The present embodiment addresses the problems faced by surface toner additives such as silicon tetrachloride (SiCl 4 ) and silica (SiO 2 ) and mixed strontium titanate (SrTiO 3 ) on the toner particles. 4 ) and silica (SiO 2 ) and mixed strontium titanate (SrTiO 3 The nominal amount of ) is 0.2 to 1.1 pph (parts per million), or in embodiments, 0.3 to 1.0 pph, or 0.4 pph to 1.0 pph. Emulsion Aggregation Toner
[0019] In an embodiment, the latex polymer may be composed of a first and a second monomer composition. Any suitable monomer or mixture of monomers may be selected to prepare the first and second monomer compositions. The selection of the monomer or mixture of monomers for the first monomer composition is independent of the selection for the second monomer composition, and vice versa. Exemplary monomers for the first and / or second monomer compositions include polyesters; styrene; alkyl acrylates, such as methyl acrylate, ethyl acrylate, butyl arylate, isobutyl acrylate, dodecyl acrylate, n-octyl acrylate, 2-chloroethyl acrylate, β-carboxyethyl acrylate (β-CEA), phenyl acrylate, methyl alpha chloroacrylate, methyl methacrylate, ethyl methacrylate, and butyl methacrylate; butadiene; isoprene; methacrylonitrile; acrylonitrile; vinyl ethers, such as vinyl methyl ether, vinyl isobutyl ether, vinyl ethyl ether, and the like; vinyl esters, For example, vinyl acetate, vinyl propionate, vinyl benzoate and vinyl butyrate; vinyl ketones, such as vinyl methyl ketone, vinyl hexyl ketone and methyl isopropenyl ketone; vinylidene halides, such as vinylidene chloride and vinylidene chlorofluoride; N-vinyl indole; N-vinyl pyrrolidone; methacrylate; acrylic acid; methacrylic acid; acrylamide; methacrylamide; vinyl pyridine; vinyl pyrrolidone; vinyl-N-methylpyridinium chloride; vinyl naphthalene; P-chlorostyrene; vinyl chloride; vinyl bromide; vinyl fluoride; ethylene; propylene; butane; isobutylene, etc., or mixtures thereof. When a mixture of monomers is used, typically the latex polymer is a copolymer.
[0020] In some embodiments, the first monomer composition and the second monomer composition can, independently of each other, comprise two or more different monomers, and thus the latex polymer can comprise a copolymer. Illustrative examples of such latex copolymers include poly(styrene-n-butyl acrylate-β-CEA), poly(styrene-alkyl acrylate), poly(styrene-1,3-diene), poly(styrene-alkyl methacrylate), poly(alkyl methacrylate-alkyl acrylate), poly(alkyl methacrylate-aryl acrylate), poly(aryl methacrylate-alkyl acrylate), poly(alkyl methacrylate), poly(styrene-alkyl acrylate-acrylonitrile), poly(styrene-1,3-diene acrylonitrile), poly(alkyl acrylate-acrylonitrile), poly(styrene-butadiene), poly(methylstyrene-butadiene), poly(methyl methacrylate-butadiene), poly(ethyl methacrylate-butadiene), poly(propyl methacrylate-butadiene), poly(butyl ... acrylate-butadiene), poly(methyl acrylate-butadiene), poly(ethyl acrylate-butadiene), poly(propyl acrylate-butadiene), poly(butyl acrylate-butadiene), poly(styrene-isoprene), poly(methyl styrene-isoprene), poly(methyl methacrylate-isoprene), poly(ethyl methacrylate-isoprene), poly(propyl methacrylate-isoprene), poly(butyl methacrylate-isoprene), poly(methyl acrylate-isoprene), poly(ethyl acrylate-isoprene), poly(propyl acrylate-isoprene), poly(butyl acrylate-isoprene); poly(styrene-propyl acrylate), poly(styrene-butyl acrylate), poly(styrene-butadiene-acrylonitrile), or polystyrene butyl acrylate-acrylonitrile).
[0021] In embodiments, the first and second monomer compositions may be substantially water insoluble, e.g., hydrophobic, and may be dispersed in the aqueous phase with sufficient agitation when added to the reaction vessel.
[0022] The weight ratio between the first monomer composition and the second monomer composition can be in the range of about 0.1:99.9 to about 50:50, for example, about 0.5:99.5 to about 25:75, about 1:99 to about 10:90.
[0023] In an embodiment, the first monomer composition and the second monomer composition may be the same. An example of the first and second monomer compositions may be a mixture containing styrene and an alkyl acrylate, such as a mixture containing styrene, n-butyl acrylate, and β-CEA. Based on the total weight of the monomers, styrene may be present in an amount of about 1% to about 99%, about 50% to about 95%, about 70% to about 90%, but may be present in a greater or lesser amount, and an alkyl acrylate, such as n-butyl acrylate, may be present in an amount of about 1% to about 99%, about 5% to about 50%, about 10% to about 30%, but may be present in a greater or lesser amount.
[0024] In embodiments, the resin may be a polyester resin, such as an amorphous resin, a crystalline resin, and / or a combination thereof, including those described in U.S. Patent Nos. 6,593,049 and 6,756,176, the disclosures of each of which are incorporated herein by reference in their entirety. Suitable resins may include mixtures of amorphous and crystalline polyester resins as described in U.S. Patent No. 6,830,860, the disclosure of which is incorporated herein by reference in its entirety.
[0025] In embodiments, the resin may be a polyester resin formed by reacting a diol and a diacid in the presence of an optional catalyst. Suitable organic diols for forming the crystalline polyester include aliphatic diols having from about 2 to about 36 carbon atoms, such as 1,2-ethanediol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, or 1,12-dodecanediol; sodio-2-sulfo-1,2-ethanediol, lithio-2-sulfo-1,2-ethanediol, potassio-2-sulfo-1,2-ethanediol, sodio-2-sulfo-1,3-propanediol, lithio-2-sulfo-1,3-propanediol, potassio-2-sulfo-1,3-propanediol, or any mixture thereof. The aliphatic diol may be selected in an amount of, for example, from about 40 to about 60 mole percent, in embodiments from about 42 to about 55 mole percent, and in embodiments from about 45 to about 53 mole percent of the resin (although amounts outside these ranges can be used), and the alkali sulfo-aliphatic diol may be selected in an amount of from about 0 to about 10 mole percent, and in embodiments from about 1 to about 4 mole percent of the resin.
[0026] Examples of organic diacids or diesters, including vinyl diacids or vinyl diesters, selected for the preparation of crystalline resins include oxalic acid, succinic acid, glutaric acid, adipic acid, suberic acid, azelaic acid, sebacic acid, fumaric acid, dimethyl fumarate, dimethyl itaconate, cis, 1,4-diacetoxy-2-butene, diethyl fumarate, diethyl maleate, phthalic acid, isophthalic acid, terephthalic acid, naphthalene-2,6-dicarboxylic acid, naphthalene-2,7-dicarboxylic acid, cyclohexanedicarboxylic acid, malonic acid, and mesaconic acid, their diesters or anhydrides; and alkali sulfo-organic diacids, such as dimethyl-5-sulfo-isophthalate, dialkyl-5-sulfo-isophthalate-4-sulfo-1,8-naphthalic anhydride, 4-sulfo-phthalic acid, dimethyl-4-sulfo-isophthalate, dimethyl-5 ... and mixtures thereof. The organic diacid may be selected in an amount of, for example, from about 40 to about 60 mole percent, in embodiments from about 42 to about 52 mole percent, and in embodiments from about 45 to about 50 mole percent of the resin, and the alkali sulfur-aliphatic diacid may be selected in an amount of from about 1 to about 10 mole percent of the resin.
[0027] Examples of the crystalline resin include polyester, polyamide, polyimide, polyolefin, polyethylene, polybutylene, polyisobutyrate, ethylene-propylene copolymer, ethylene-vinyl acetate copolymer, polypropylene, or any mixture thereof. A specific crystalline resin may be a polyester, such as poly(ethylene-adipate), poly(propylene-adipate), poly(butylene-adipate), poly(pentylene-adipate), poly(hexylene-adipate), poly(octylene-adipate), poly(ethylene-succinate), poly(propylene-succinate), poly(butylene-succinate), poly(pentylene-succinate), poly(hexylene-succinate), poly(octylene-succinate ... cyanate), poly(ethylene sebacate), poly(propylene sebacate), poly(butylene sebacate), poly(pentylene sebacate), poly(hexylene sebacate), poly(octylene sebacate), poly(decylene sebacate), poly(decylene decanoate), poly(ethylene decanoate), poly(ethylene dodecanoate), poly(nonylene sebacate), poly(nonylene dodecanoate), copoly(ethylene fumarate)-copoly (ethylene-sebacate), copoly(ethylene-fumarate)-eopoly(ethylene-decanoate), copoly(ethylene-fumarate)-copoly(ethylene-dodecanoate), copoly(5-sulfoisophthaloyl)-copoly(ethylene-adipate), alkali copoly(5-sulfoisophthaloyl)-copoly(propylene-adipate), alkali copoly(5-sulfoisophthaloyl)-copoly(butylene-adipate), alkali copoly(5-sulfoisophthaloyl)-copoly(ethylene-adipate), alkali copoly(5-sulfoisophthaloyl)-copoly(propylene-adipate), alkali copoly(5-sulfoisophthaloyl)-copoly(butylene-adipate), alkali copoly(5-sulfoisophthaloyl)- copoly(pentylene-adipate), alkali copoly(5-sulfo-isophthaloyl)-copoly(hexylene-adipate), alkali copoly(5-sulfo-isophthaloyl)-copoly(octylene-adipate), alkali copoly(5-sulfo-isophthaloyl)-copoly(ethylene-adipate), alkali copoly(5-sulfo-isophthaloyl)-copoly(propylene-adipate), alkali copoly(5-sulfo-isophthaloyl)-copoly(butylene-adipate),Alkaline copoly(5-sulfoisophthaloyl)-copoly(pentylene adipate), alkali copoly(5-sulfoisophthaloyl)-copoly(hexylene adipate), alkali copoly(5-sulfoisophthaloyl)-copoly(octylene adipate), alkali copoly(5-sulfoisophthaloyl)-copoly(ethylene succinate), alkali copoly(5-sulfoisophthaloyl)-copoly(propylene succinate), alkali copoly(5-sulfoisophthaloyl)-copoly(ethylene succinate), Alkaline copoly(5-sulfoisophthaloyl)-copoly(butylene succinate), alkaline copoly(5-sulfoisophthaloyl)-copoly(pentylene succinate), alkaline copoly(5-sulfoisophthaloyl)-copoly(hexylene succinate), alkaline copoly(5-sulfoisophthaloyl)-copoly(octylene succinate), alkaline copoly(5-sulfoisophthaloyl)-copoly(ethylene sebacate), alkaline copoly(5-sulfoisophthaloyl)-copoly(ethylene sebacate), Alkaline copoly(propylene-sebacate), alkali copoly(5-sulfo-isophthaloyl)-copoly(butylene-sebacate), alkali copoly(5-sulfo-isophthaloyl)-copoly(pentylene-sebacate), alkali copoly(5-sulfo-isophthaloyl)-copoly(hexylene-sebacate), alkali copoly(5-sulfo-isophthaloyl)-copoly(octylene-sebacate), alkali copoly(5-sulfo-isophthaloyl)-copoly(ethylene-adipate) ), alkali copoly(5-sulfo-isophthaloyl)-copoly(propylene-adipate), alkali copoly(5-sulfo-isophthaloyl)-copoly(butylene-adipate), alkali copoly(5-sulfo-isophthaloyl)-copoly(pentylene-adipate), alkali copoly(5-sulfo-isophthaloyl)-copoly(hexylene-adipate), poly(octylene-adipate), where alkali is a metal such as sodium, lithium or potassium. Examples of polyamides include poly(ethylene-adipamide), poly(propylene-adipamide), poly(butylene-adipamide), poly(pentylene-adipamide), poly(hexylene-adipamide), poly(ethylene-adipamide), poly(ethylene-succinimide), and poly(propylene-sebacamide), butNon-limiting examples of polyimides include poly(ethylene-adipimide), poly(propylene-adipimide), poly(butylene-adipimide), poly(pentylene-adipimide), poly(hexylene-adipimide), poly(octylene-adipimide), poly(ethylene-succinimide), poly(propylene-succinimide), and poly(butylene-succinimide).
[0028] The crystalline resin may be present in an amount of, for example, from about 5 to about 50 weight percent of the toner components, and in embodiments, from about 10 to about 35 weight percent of the toner components. The crystalline resin may have a variety of melting points, for example, from about 30° C. to about 120° C., and in embodiments, from about 50° C. to about 90° C. The crystalline resin may have a number average molecular weight (M) of, for example, from about 1,000 to about 50,000, and in embodiments, from about 2,000 to about 25,000, as measured by gel permeation chromatography (GPC) using polystyrene standards. n ), and a weight average molecular weight (M) of about 2,000 to about 100,000, and in embodiments, about 3,000 to about 80,000, as measured by GPC. w The molecular weight distribution (M w / M n ) may be, for example, about 2 to about 6, and in embodiments, about 3 to about 4.
[0029] Examples of diacids or diesters, including vinyl diacids or vinyl diesters, that may be utilized in the preparation of the amorphous polyesters include dicarboxylic acids or diesters, such as terephthalic acid, phthalic acid, isophthalic acid, fumaric acid, dimethyl fumarate, dimethyl itaconate, cis 1,4-diacetoxy-2-butene, diethyl fumarate, diethyl maleate, maleic acid, succinic acid, itaconic acid, succinic acid, succinic anhydride, dodecyl succinic acid, dodecyl succinic anhydride, glutaric acid, anhydrous carboxylic acid, ... The organic diacid or diester may be present in an amount of, for example, from about 40 to about 60 mole percent of the resin, in embodiments from about 42 to about 52 mole percent of the resin, and in embodiments from about 45 to about 50 mole percent of the resin. Examples of alkylene oxide adducts of bisphenols include, but are not limited to, polyoxypropylene(2.2)-2,2-bis(4-hydroxyphenyl)propane, polyoxypropylene(3.3)-2,2-bis(4-hydroxyphenyl)propane, polyoxyethylene(2.0)-2,2-bis(4-hydroxyphenyl)propane, polyoxyethylene(2.2)-2,2-bis(4-hydroxyphenyl)propane, polyoxypropylene(2.0)-polyoxyethylene(2.0)-2,2-bis(4-hydroxyphenyl)propane, and polyoxypropylene(6)-2,2-bis(4-hydroxyphenyl)propane. These compounds may be used alone or in combination of two or more thereof.
[0030] Examples of additional diols that may be utilized in producing the amorphous polyester include, but are not limited to, 1,2-propanediol, 1,3-propanediol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, pentanediol, hexanediol, 2,2-dimethylpropanediol, 2,2,3-trimethylhexanediol, heptanediol, dodecanediol, 1,4-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, xylenediethanol, cyclohexanediol, diethylene glycol, dipropylene glycol, dibutylene, or any combination thereof. The amount of organic diol selected may vary, and may be present, for example, in an amount of from about 40 to about 60 mole percent of the resin, in embodiments from about 42 to about 55 mole percent of the resin, in embodiments from about 45 to about 53 mole percent of the resin.
[0031] Polycondensation catalysts that may be utilized to form either crystalline or amorphous polyesters include, but are not limited to, tetraalkyl titanates, dialkyl tin oxides such as dibutyl tin oxide, tetraalkyl tins such as dibutyl tin dilaurate, and dialkyl tin oxide hydroxides such as butyl tin oxide hydroxide, aluminum alkoxides, alkyl zincs, dialkyl zincs, zinc oxides, stannous oxides, or any combination thereof. Such catalysts may be utilized, for example, in amounts of about 0.01 mole percent to about 5 mole percent based on the starting diacid or diester used to produce the polyester resin.
[0032] In embodiments, suitable amorphous resins include polyesters, polyamides, polyimides, polyolefins, polyethylene, polybutylene, polyisobutyrate, ethylene-propylene copolymers, ethylene-vinyl acetate copolymers, polypropylene, or any combination thereof. Examples of amorphous resins that may be utilized include, but are not limited to, alkali sulfonated polyester resins, branched alkali sulfonated polyester resins, alkali sulfonated polyimide resins, or branched alkali sulfonated polyimide resins. Alkali sulfonated polyester resins may be useful in embodiments, including copoly(ethylene-terephthalate)-copoly(ethylene-5-sulfo-isophthalate), copoly(propylene-terephthalate)-copoly(propylene-5-sulfo-isophthalate), copoly(diethylene-terephthalate)-copoly(diethylene-5-sulfo-isophthalate), copoly(propylene-diethylene-terephthalate)-copoly(propylene-diethylene-5-sulfoisophthalate), copoly(propylene-butylene-terephthalate)-copoly(propylene-butylene-terephthalate), and the like. and the metal or alkali salts of copoly(ethoxylated bisphenol-A-maleate)-copoly(ethoxylated bisphenol-A-5-sulfoisophthalate), copoly(propoxylated biphenol-A-fumarate)-copoly(propoxylated bisphenol-A-5-sulfo-isophthalate), copoly(ethoxylated bisphenol-A-fumarate)-copoly(ethoxylated bisphenol-A-5-sulfo-isophthalate), where the alkali metal is, for example, sodium ion, lithium ion, or potassium ion.
[0033] In embodiments, as described above, unsaturated amorphous polyester resins may be utilized as latex resins. Examples of such resins include those disclosed in U.S. Patent No. 6,063,827, the disclosure of which is incorporated herein by reference in its entirety. Exemplary unsaturated amorphous polyester resins include poly(propoxylated bisphenol co-fumarate), poly(ethoxylated bisphenol co-fumarate), poly(butyloxylated bisphenol co-fumarate), poly(copropoxylated bisphenol co-ethoxylated bisphenol co-fumarate), poly(1,2-propylene fumarate), poly(propoxylated bisphenol co-maleate), poly(ethoxylated bisphenol co-maleate), poly(butyloxylated bisphenol co-maleate). , poly(copropoxylated bisphenol co-ethoxylated bisphenol co-maleate), poly(1,2-propylene maleate), poly(propoxylated bisphenol co-itaconate), poly(ethoxylated bisphenol co-itaconate), poly(butyloxylated bisphenol co-itaconate), poly(copropoxylated bisphenol co-ethoxylated bisphenol co-itaconate), poly(1,2-propylene itaconate), or any combination thereof.
[0034] Further, in an embodiment, a crystalline polyester resin may be included in the binder resin. The crystalline polyester resin may be synthesized from an acid (dicarboxylic acid) component and an alcohol (diol) component. Hereinafter, the term "acid-derived component" refers to the component portion that was originally an acid component before the synthesis of the polyester resin, and the term "alcohol-derived component" refers to the component portion that was originally an alcohol component before the synthesis of the polyester resin.
[0035] "Crystalline polyester resin" refers to a resin that does not show a stepwise change in endothermic amount but shows a clear endothermic peak in differential scanning calorimetry (DSC). However, a polymer obtained by copolymerizing a crystalline polyester backbone with at least one other component can also be called a crystalline polyester when the amount of the other component is 50% or less.
[0036] The acid-derived component may be an aliphatic dicarboxylic acid such as a straight-chain carboxylic acid. Examples of straight-chain carboxylic acids include, but are not limited to, oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, 1,9-nonanedicarboxylic acid, 1,10-decanedicarboxylic acid, 1,1-undecanedicarboxylic acid, 1,12-dodecanedicarboxylic acid, 1,13-tridecanedicarboxylic acid, 1,14-tetradecanedicarboxylic acid, 1,16-hexadecanedicarboxylic acid, or 1,18-octadecanedicarboxylic acid, as well as lower alkyl esters and anhydrides thereof. Among these, acids having 6 to 10 carbon atoms may be desirable to obtain suitable crystalline melting points and charging properties. To improve crystallinity, the straight-chain carboxylic acid may be present in an amount of about 95 mole percent or more of the acid component, and in embodiments, may be present in an amount of more than about 98 mole percent of the acid component. The other acid is not particularly limited, and examples thereof include conventionally known divalent carboxylic acids and dihydric alcohols. Specific examples of the monomer component include dibasic acids such as phthalic acid, isophthalic acid, terephthalic acid, naphthalene-2,6-dicarboxylic acid, naphthalene-2,7-dicarboxylic acid, or cyclohexanedicarboxylic acid, or their anhydrides and lower alkyl esters, and any combinations thereof, as divalent carboxylic acids. As acid-derived components, components such as dicarboxylic acid-derived components having sulfonic acid groups can also be used. Dicarboxylic acids having sulfonic acid groups can be effective in obtaining excellent dispersion of colorants such as pigments. Furthermore, when the entire resin is emulsified or suspended in water to prepare the toner base particles, the sulfonic acid groups can emulsify or suspend the resin without using a surfactant. Examples of such dicarboxylic acids having sulfonic acid groups include, but are not limited to, sodium 2-sulfoterephthalate, sodium 5-sulfoisophthalate, and sodium sulfosuccinate. Further, for example, lower alkyl esters and acid anhydrides of such dicarboxylic acids having sulfonic acid groups may also be used. Among these, sodium 5-sulfoisophthalate and the like may be desirable in consideration of cost.The content of the dicarboxylic acid having a sulfonic acid group may be about 0.1% to about 2 mol percent, and in embodiments, about 0.2 mol percent to about 1 mol percent. If the content exceeds about 2 mol percent, the charging characteristics may deteriorate. Here, "component mol %" or "component mole %" indicates the ratio when the total amount of each component (acid-derived component and alcohol-derived component) in the polyester resin is assumed to be 1 unit (mole).
[0037] As the alcohol component, an aliphatic diol may be used. Examples thereof include, but are not limited to, ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 6-hexanediol, 1,7 heptanediol, 1,8 octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-dodecanediol, 1,12-undecanediol, 1,13-tridecanediol, 1,14-tetradecanediol, 1,18-octadecanediol, or 1,20-eicosadiol. Among these, those having about 6 to about 10 carbon atoms can be used to obtain desirable crystalline melting points and charging properties. To increase the degree of crystallinity, it may be useful to use linear diols in an amount of about 95 mole percent or more, in embodiments about 98 mole percent or more.
[0038] Examples of other dihydric diols that may be utilized include, but are not limited to, bisphenol A, hydrogenated bisphenol A, bisphenol A ethylene oxide adducts, bisphenol A propylene oxide adducts, 1,4-cyclohexanediol, 1,4-cyclohexanedimethanol, diethylene glycol, propylene glycol, dipropylene glycol, 1,3-butanediol, neopentyl glycol, and combinations thereof.
[0039] To adjust the acid value and hydroxyl value, monovalent acids such as acetic acid and benzoic acid; monohydric alcohols such as cyclohexanol and benzyl alcohol; benzenetricarboxylic acid, naphthalenetricarboxylic acid, and their anhydrides and lower alkyl esters; trihydric alcohols such as glycerin, trimethylolethane, trimethylolpropane, pentaerythritol, and any combination thereof may be used.
[0040] The crystalline polyester resin can be synthesized from a combination of components selected from the above monomer components by using conventional methods. Exemplary methods include transesterification and direct polycondensation, which can be used alone or in combination. The molar ratio (acid component / alcohol component) when reacting the acid component and the alcohol component can vary depending on the reaction conditions. The molar ratio is usually about 1 / 1 in direct polycondensation. The transesterification method may use an excess of monomers such as ethylene glycol, neopentyl glycol, or cyclohexane dimethanol, which can be distilled under vacuum. Surfactants
[0041] Any suitable surfactant may be used in preparing the latex and wax dispersions according to the present disclosure. Depending on the emulsion system, any desired non-ionic or ionic surfactant, such as anionic or cationic surfactants, may be contemplated.
[0042] Examples of suitable anionic surfactants include, but are not limited to, sodium dodecyl sulfate, sodium dodecylbenzene sulfate, sodium dodecylnaphthalene sulfate, dialkylbenzene alkyl sulfates and sulfonates, abitinic acid, NEOGEN R® and NEOGEN SC® available from Kao, Tayca Power® available from Tayca Corp., DOWFAX® available from Dow Chemical Co., and the like, and mixtures thereof. The anionic surfactant can be present in any desired or effective amount, such as at least about 0.01% by weight of the total monomers used to prepare the latex polymer, at least about 0.1% by weight of the total monomers used to prepare the latex polymer, up to about 10% by weight of the total monomers used to prepare the latex polymer, up to about 5% by weight of the total monomers used to prepare the latex polymer, although these amounts can also be outside these ranges.
[0043] Other examples of suitable cationic surfactants include dialkylbenzene alkyl ammonium chloride, lauryl trimethyl ammonium chloride, alkyl benzyl methyl ammonium chloride, alkyl benzyl dimethyl ammonium bromide, benzalkonium chloride, cetyl pyridinium bromide, C 12 , C 15 and C 17 These include, but are not limited to, trimethylammonium bromide, halogen salts of quaternized polyoxyethylalkylamines, dodecylbenzyltriethylammonium chloride, MIRAPOL® and ALKAQUAT® (available from Alkaril Chemical Company), SANIZOL® (benzalkonium chloride, available from Kao Chemicals), and the like, and any mixtures thereof.
[0044] Examples of suitable nonionic surfactants include, but are not limited to, polyvinyl alcohol, polyacrylic acid, methalose, methylcellulose, ethylcellulose, propylcellulose, hydroxyethylcellulose, carboxymethylcellulose, polyoxyethylene cetyl ether, polyoxyethylene lauryl ether, polyoxyethylene octyl ether, polyoxyethylene octylphenyl ether, polyoxyethylene oleyl ether, polyoxyethylene sorbitan monolaurate, polyoxyethylene stearyl ether, polyoxyethylene nonylphenyl ether, dialkylphenoxypoly(ethyleneoxy)ethanols (available from Rhone-Poulenc as IGEPAL CA-210®, IGEPAL CA-520®, IGEPAL CA-720®, IGEPAL CO-890®, IGEPAL CO-720®, IGEPAL CO-290®, IGEPAL CA-210®, ANTAROX 890®, and ANTAROX 897®), and the like, and any mixtures thereof. Initiator
[0045] Any suitable initiator or mixture of initiators can be selected in the latex and toner processes. In embodiments, the initiator is selected from known free radical polymerization initiators. The free radical initiator can be any free radical polymerization initiator or any mixture thereof that can initiate a free radical polymerization process, and such free radical initiator can provide free radical species when heated to above about 30°C.
[0046] Water-soluble free radical initiators are used in the emulsion polymerization reaction, but other free radical initiators can also be used. Examples of suitable free radical initiators include peroxides, such as ammonium persulfate, hydrogen peroxide, acetyl peroxide, cumyl peroxide, tert-butyl peroxide, propionyl peroxide, benzoyl peroxide, chlorobenzoyl peroxide, dichlorobenzoyl peroxide, bromomethylbenzoyl peroxide, lauroyl peroxide, diisopropyl peroxycarbonate, tetralin hydroperoxide, 1-phenyl-2-methylpropyl-1-hydroperoxide and tert-butyl hydroperoxide; pertriphenyl acetate, tert-butyl performate; tert-butyl peracetate; tert-butyl perbenzoate; tert-butyl perphenyl acetate; tert-butyl permethoxy acetate; tert-butyl / per-N-(3-tolyl)carbamate; sodium persulfate;Potassium persulfate, azo compounds such as 2,2'-azobispropane, 2,2'-dichloro-2,2'-azobispropane, 1,1'-azo(methylethyl) diacetate, 2,2'-azobis(2-amidinopropane) hydrochloride, 2,2'-azobis(2-amidinopropane)-nitrate, 2,2'-azobisisobutane, 2,2'-azobisisobutyramide, 2,2'-azobisisobutyronitrile, methyl 2,2'-azobis-2-methylpropionate, 2,2'-dichloro-2,2'-azobisbutanol, Tan, 2,2'-azobis-2-methylbutyronitrile, dimethyl 2,2'-azobisisobutyrate, sodium 1,1'-azobis(1-methylbutyronitrile-3-sulfonate), 2-(4-methylphenylazo)-2-methylmalonodinitrile, 4,4'-azobis-4-cyanovaleric acid, 3,5-dihydroxymethylphenylazo-2-methylmalonodinitrile, 2-(4-bromophenylazo)-2-allylmalonodinitrile, 2,2'-azobis-2-methylvaleronitrile, dimethyl 4,4' -Azobis-4-cyanovalerate, 2,2'-azobis-2,4-dimethylvaleronitrile, 1,1'-azobiscyclohexanenitrile, 2,2'-azobis-2-propylbutyronitrile, 1,1'-azobis-1-chlorophenylethane, 1,1'-azobis-1-cyclohexanecarbonitrile, 1,1'-azobis-1-cycloheptanenitrile, 1,1'-azobis-1-phenylethane, 1,1'-azobiscumene, ethyl 4-nitrophenylazobenzyl cyanoacetate, phenylazodi These include, but are not limited to, phenylmethane, phenylazotriphenylmethane, 4-nitrophenylazotriphenylmethane, 1'-azobis-1,2-diphenylethane, poly(bisphenol-A-4,4'-azobis-4-cyanopentano-ate) and poly(tetraethylene glycol-2,2'-azobisisobutyrate); 1,4-bis(pentaethylene)-2-tetrazene; 1,4-dimethoxycarbonyl-1,4-diphenyl-1-2-tetrazene, and the like; or any mixture thereof;
[0047] More typical free radical initiators include, but are not limited to, ammonium persulfate, hydrogen peroxide, acetyl peroxide, cumyl peroxide, tert-butyl peroxide, propionyl peroxide, benzoyl peroxide, chlorobenzoyl peroxide, dichlorobenzoyl peroxide, bromomethylbenzoyl peroxide, lauroyl peroxide, sodium persulfate, potassium persulfate, diisopropyl peroxycarbonate, and the like, or combinations thereof.
[0048] Based on the total weight of the monomers, the initiator may be present in an amount of from about 0.1% to about 5%, from about 0.4% to about 4%, from about 0.5% to about 3%, but may be present in greater or lesser amounts. Chain Transfer Agents
[0049] Chain transfer agents may optionally be used to control the degree of polymerization of the latex, and thereby the molecular weight and molecular weight distribution of the product latex of the latex process and / or toner process according to the present disclosure. As can be appreciated, the chain transfer agent can become part of the latex polymer.
[0050] In an embodiment, the chain transfer agent has a carbon-sulfur covalent bond. The carbon-sulfur covalent bond has a wavelength of 500 to 800 cm in the infrared absorption spectrum. -1 When a chain transfer agent is incorporated into the latex and the toner made from the latex, the absorption peak may be, for example, in the wave number region of 400 to 4,000 cm. -1 can be changed to the wavenumber region.
[0051] Exemplary chain transfer agents include nC 3-15Alkyl mercaptans such as n-propyl mercaptan, n-butyl mercaptan, n-amyl mercaptan, n-hexyl mercaptan, n-heptyl mercaptan, n-octyl mercaptan, n-nonyl mercaptan, n-decyl mercaptan and n-dodecyl mercaptan; branched alkyl mercaptans such as isopropyl mercaptan, isobutyl mercaptan, s-butyl mercaptan, tert-butyl mercaptan, cyclohexyl mercaptan, tert-hexadecyl mercaptan, tert-lauryl mercaptan, tert-nonyl mercaptan, tert-octyl mercaptan and tert-tetradecyl mercaptan; aromatic ring-containing mercaptans such as allyl mercaptan, 3-phenylpropyl mercaptan, phenyl mercaptan and mercaptotriphenylmethane, but are not limited thereto. The terms mercaptan and thiol can be used interchangeably to refer to the C-SH group.
[0052] Examples of such chain transfer agents include, but are not limited to, dodecanethiol, butanethiol, isooctyl-3-mercaptopropionate, 2-methyl-5-t-butyl-thiophenol, carbon tetrachloride, carbon tetrabromide, and the like, or any combination thereof.
[0053] Based on the total weight of the monomers, the chain transfer agent may be present in an amount of from about 0.1% to about 7%, from about 0.5% to about 6%, from about 1.0% to about 5%, but may be present in greater or lesser amounts.
[0054] In embodiments, a branching agent may be optionally included in the first / second monomer composition to control the branched structure of the target latex. Exemplary branching agents include, but are not limited to, decanediol diacrylate (ADOD), trimethylolpropane, pentaerythritol, trimellitic acid, pyromellitic acid, or any mixture thereof.
[0055] Based on the total weight of the monomers, the branching agent may be present in an amount of from about 0% to about 2%, from about 0.05% to about 1.0%, from about 0.1% to about 0.8%, but may be present in greater or lesser amounts.
[0056] In the latex and toner processes of the present disclosure, emulsification can be carried out by any suitable process, such as mixing at elevated temperatures. For example, the emulsion mixture can be mixed in a homogenizer set at about 200 to about 400 rpm, at a temperature of about 40° C. to about 80° C., for a time of about 1 minute to about 20 minutes.
[0057] Any type of reactor can be used without limitation. The reactor can include a means for stirring the composition therein, such as an impeller. The reactor can include at least one impeller. The reactor can be operated throughout the process such that the impeller can operate at an effective mixing speed of about 10 to about 1,000 rpm to form the latex and / or toner.
[0058] After monomer addition is complete, the latex can be stabilized by maintaining the conditions for a period of time, e.g., from about 10 minutes to about 300 minutes, before cooling. Optionally, the latex formed by the above process can be isolated by standard methods known in the art, e.g., by coagulation, dissolution and precipitation, filtration, washing, drying, etc.
[0059] The latexes of the present disclosure may be selected for emulsion-aggregation-coalescence processes to form toners and developers by known methods. The latexes of the present disclosure may be melt blended or otherwise mixed with various toner formulation ingredients, such as wax dispersions, coagulants, optional silica, optional charge enhancing or control additives, optional surfactants, optional emulsifiers, optional flow additives, and the like. Optionally, the latexes (e.g., about 40% solids by weight) may be diluted to a desired solids loading (e.g., about 12 to about 15% solids by weight) before being formulated into a toner composition.
[0060] Based on the total weight of the toner, the latex may be present in an amount of from about 50% to about 100%, from about 60% to about 98%, from about 70% to about 95%, but may also be present in greater or lesser amounts. Coloring agent
[0061] A variety of known suitable colorants can be included in the toner, such as dyes, pigments, mixtures of dyes, mixtures of pigments, mixtures of dyes and pigments, etc. The colorant can be included in the toner in an amount of, for example, from about 0.1 to about 35% by weight of the toner, from about 1 to about 15% by weight of the toner, or from about 3 to about 10% by weight of the toner, although amounts outside these ranges can also be utilized.
[0062] Examples of suitable colorants may include carbon black-like REGAL 330®; magnetite, such as Mobay magnetite MO8029™ and MO8060™; Columbian magnetite; MAPICO BLACKS™, surface-treated magnetite; Pfizer magnetite CB4799™, CB5300™, CB5600™, and MCX6369™; Bayer magnetite, BAYFERROX8600™ and 8610™; Northern Pigments magnetite, NP-604™ and NP-608™; Magnox magnetite TMB-100™ or TMB-104™, and the like. Colored pigments may be selected from cyan, magenta, yellow, red, green, brown, blue, or mixtures thereof. Generally, cyan, magenta, or yellow pigments or dyes, or mixtures thereof, are used. The pigment or pigments may be used as a water-based pigment dispersion.
[0063] Specific examples of pigments include: SUNSPERSE 6000, FLEXIVERSE and AQUATONE aqueous pigment dispersions from SUN Chemicals; HELIOGEN BLUE L6900™, D6840™, D7080™, D7020™, PYLAM OIL BLUE™, PYLAM OIL YELLOW™, PIGMENT BLUE I™ available from Paul Uhlich & Company, Inc.; PIGMENT VIOLET 1™, PIGMENT RED 48™, LEMON CHROME YELLOW DCC 1026™, EDTOLUIDINE RED™ and BON RED C™ available from Dominion Color Corporation, Ltd. (Toronto, Ontario); NOVAPERM YELLOW FGL™, HOSTAPERM PINKE™ available from Hoechst; and CINQUASIA MAGENTA™ available from de Nemours & Company. Colorants that may be selected are black, cyan, magenta, yellow, and mixtures thereof. Examples of magenta include, but are not limited to, 2,9-dimethyl-substituted quinacridone and anthraquinone dyes identified in the Color Index as CI 60710, CI Dispersed Red 15, diazo dyes identified in the Color Index as CI 26050, CI Solvent Red 19, and the like. Illustrative examples of cyan include, but are not limited to, copper tetra(octadecylsulfonamido)phthalocyanine, x-copper phthalocyanine pigments listed in the Color Index as CI 74160, CI Pigment Blue, Pigment Blue 15:3, Anthrathrene Blue identified in the Color Index as CI 69810, Special Blue X-2137, and the like. Illustrative examples of yellow include diarylide yellow 3,Examples include, but are not limited to, 3-dichlorobenzidene acetoacetanilide, a monoazo pigment identified in the Color Index as CI 12700, CI Solvent Yellow 16, nitrophenylamine sulfonamide identified in the Color Index as Foron Yellow SE / GLN, CI Dispersed Yellow 33, 2,5-dimethoxy-4-sulfonanilide phenylazo-4'-chloro-2,5-dimethoxyacetoacetanilide, and Permanent Yellow FGL. Colored magnetites, such as a mixture of MAPICO BLACK™ and a cyan component, may also be selected as colorants. For example, Levanyl Black A-SF (Miles, Bayer) and Sunsperse Carbon Black LHD 9303 (Sun Chemicals), and color dyes such as Neopen Blue (BASF), Sudan Blue OS (BASF), PV FAST Blue B2G01 (American Hoechst), Sunsperse Blue BHD 6000 (Sun Chemicals), Irgalite Blue BCA (Ciba-Geigy), Paliogen Blue 6470 (BASF), Sudan III (Matheson, Coleman, Bell), Sudan II (Matheson, Coleman, Bell), Sudan IV (Matheson, Coleman,Bell), Sudan Orange G(Aldrich), Sudan Orange 220(BASF), Paliogen Orange 3040(BASF), Ortho Orange OR 2673(Paul Uhlich), Paliogen Yellow 152, 1560(BASF), Lithol Fast Yellow 0991K(BASF), Paliotol Yellow 1840(BASF), Neopen Yellow(BASF), Novoperm Yellow FG 1(Hoechst), Permanent Yellow YE 0305(Paul Uhlich), Lumogen Yellow D0790(BASF), Sunsperse Yellow YHD 6001(Sun Chemicals), Suco Gelb L1250(BASF), Suco Yellow D1355(BASF), Hostaperm Pink E(American Hoechst), Fanal Pink D4830(BASF), Cinquasia Other known colorants may be used, such as Magenta (DuPont), Lithol Scarlet D3700 (BASF), Toluidine Red (Aldrich), Scarlet for Thermoplast NSD PS PA (Ugine Kuhlmann, Canada), ED Toluidine Red (Aldrich), Lithol Rubine Toner (Paul Uhlich), Lithol Scarlet 4440 (BASF), Bon Red C (Dominion Color Company), Royal Brilliant Red RD-8192 (Paul Uhlich), Oracet Pink RF (Ciba-Geigy), Paliogen Red 3871K (BASF), Paliogen Red 3340 (BASF), Lithol Fast Scarlet L4300 (BASF), and any combination of the above. wax
[0064] In addition to the polymer resin, the toner of the present disclosure may also contain a wax, which may be either a single type of wax or a mixture of two or more different waxes. For example, a single wax may be added to the toner composition to improve a particular toner property, such as the shape of the toner particles, the presence and amount of wax on the toner particle surface, charging and / or fusing properties, gloss, stripping, offset properties, etc. Alternatively, a combination of waxes may be added to provide multiple properties to the toner composition.
[0065] If included, the wax may be present in an amount of, for example, from about 1% to about 25% by weight of the toner particles, in embodiments from about 5% to about 20% by weight of the toner particles.
[0066] Waxes that may be selected include, for example, waxes having a weight average molecular weight of about 500 to about 20,000, in embodiments from about 1,000 to about 10,000. Waxes that may be used include, for example, polyolefins such as polyethylene, polypropylene, and polybutene waxes, such as those commercially available from Allied Chemical and Petrolite Corporation, e.g., POLYWAX™ polyethylene wax from BAKER Petrolite, wax emulsions available from Michaelman, Inc. and Daniels Products Company, EPOLENE N-15™, available from Eastman Chemical Products, Inc., and VISCOL, a low weight average molecular weight polypropylene available from Sanyo Kasei KK. 550-P (trademark); vegetable waxes such as carnauba wax, rice wax, candelilla wax, sumac wax, and jojoba oil; animal waxes such as beeswax; mineral and petroleum waxes such as montan wax, ozokerite, ceresin, paraffin wax, microcrystalline wax, and Fischer-Tropsch wax; ester waxes obtained from higher fatty acids and higher alcohols such as stearyl stearate and behenyl behenate; ester waxes obtained from higher fatty acids and monohydric or polyhydric lower alcohols such as butyl stearate, propyl oleate, glyceride monostearate, glyceride distearate, and pentaerythritol tetrabehenate; ester waxes obtained from higher fatty acids and polyhydric alcohol multimers such as diethylene glycol monostearate, dipropylene glycol distearate, diglyceryl distearate, and triglyceryl tetrastearate; sorbitan higher fatty acid ester waxes such as sorbitan monostearate, and cholesterol higher fatty acid ester waxes such as cholesteryl stearate.Examples of functionalized waxes that may be used include, for example, amines, amides such as AQUA SUPERSLIP 6550™, SUPERSLIP 6530™ available from Micro Powder Inc., fluorinated waxes such as POLYFLUO 190™, POLYFLUO 200™, POLYSILK 19™, POLYSILK 14™ available from Micro Powder Inc., mixed fluorinated amide waxes such as MICROSPERSION 19™ available from Micro Powder Inc., imide, ester, quaternary amine, carboxylic acid, or acrylic polymer emulsions such as JONCRYL 74™, 89™, 130™, 537™, and 538™ all available from SC Johnson Wax, as well as other waxes available from Allied Chemical, Petrolite Corporation, and SC Johnson. Waxes include chlorinated polypropylene and polyethylene available from Wax, and mixtures and combinations of the foregoing waxes may also be used in embodiments. Waxes may be included, for example, as fuser roll release agents. Charge control agent (CCA)
[0067] Charge control agents may be incorporated into the surface additive. In embodiments, the charge control agent is a metallic charge control agent having metals such as zinc, aluminum, calcium, chromium, and iron. In embodiments, the charge control agent is 3,5 di-tert-butyl salicylic acid zinc salt. Suitable zinc charge control agents include BONTRON E-84™, BONTRON E-84S™, or BONTRON E-304™ (Hodogaya Chemical) and similar zinc salts. In embodiments, charge control agent aluminum salts, such as BONTRON E-108™ or BONTRON E-108W™ (Hodogaya Chemical), are suitable. In embodiments, charge control agents or iron complexes, such as BONTRON X-11™ (Hodogaya Chemical), are suitable. Charge control agents may include combinations of those listed above. In embodiments, charge control agents or chromium complexes, such as BONTRON E-81™ or BONTRON S-34™ (Hodogaya Chemical), are suitable. The charge control agent may include combinations of those listed above. The particle size of the charge control agent may be adjusted to a particle size of about 50 to about 500, or about 150 to about 300, or about 175 to about 275 nm, in embodiments. In embodiments, the CCA and silicone oil may have reversed nucleophilic and electrophilic capacities. For example, the silicone oil may be modified to present a nucleophilic amino group, which may then be alkylated to produce a quaternary ammonium salt.
[0068] The charge control agent can be incorporated into the core of the particle, the shell of the particle, or a combination of both. If placed in the core, the CCA is added during homogenization, but just prior to the addition of the coagulant. The mixture is then homogenized according to procedure, and the batch is then heated, agglomerated, and coalesced. If added to the shell, or both the core and shell, the CCA should be added first to the shell latex before adding to the shell. The shell mixture is added by pump until complete. The process then proceeds similarly to the control sample. The charge control agent is present in the toner in an amount of about 0.1 to about 3, or about 0.3 to 2, or about 0.3 to 1 weight percent of the total solids.
[0069] Silicon tetrachloride (SiCl 4 The incorporation of CCA into toners using ) can be used as a toner additive and toner formulation. Toner Preparation
[0070] The toner particles may be prepared by any method within the purview of one skilled in the art. Although embodiments relating to the manufacture of toner particles are described below with respect to an emulsion-aggregation process, any suitable method of preparing toner particles may be used, including chemical processes such as suspension and encapsulation methods disclosed in U.S. Patent Nos. 5,290,654 and 5,302,486, the disclosures of each of which are incorporated herein by reference in their entirety. In embodiments, the toner compositions and particles may be prepared by an aggregation and coalescence process, in which small resin particles are aggregated to the appropriate toner particle size and then coalesced to achieve the final toner particle shape and morphology.
[0071] In embodiments, the toner composition may be prepared by an emulsion-aggregation process, such as a process that includes aggregating a mixture of optional wax and any other desired or required additives with an emulsion containing the resin described above, optionally with a surfactant, as described above, and then combining the aggregated mixture. The mixture may be prepared by adding optional wax or other materials (which may also be present in a dispersion, optionally with a surfactant), to the emulsion (which may be a mixture of two or more emulsions containing the resin). The pH of the resulting mixture may be adjusted with an acid (i.e., a pH adjuster), such as, for example, acetic acid, nitric acid, and the like. In embodiments, the pH of the mixture may be adjusted to about 2 to about 4.5. Additionally, in embodiments, the mixture may be homogenized. If the mixture is homogenized, homogenization may be achieved by mixing at about 600 to about 4,000 revolutions per minute (rpm). Homogenization may be accomplished by any suitable means, including, for example, an IKA ULTRA TURRAX T50 probe homogenizer.
[0072] Following preparation of the mixture, a flocculant may be added to the mixture. Suitable flocculants include, for example, an aqueous solution of a divalent cation or polyvalent cation material. Flocculants may include, but are not limited to, polyaluminum halides, such as polyaluminum chloride (PAC), or the corresponding bromides, fluorides, or iodides, polyaluminum silicates, such as polyaluminum sulfosilicate (PASS), and water-soluble metal salts, including aluminum chloride, aluminum nitrite, aluminum sulfate, aluminum sulfate, calcium chloride, calcium nitrite, calcium oxyacids, calcium sulfate, magnesium acetate, magnesium nitrate, magnesium sulfate, zinc acetate, zinc nitrate, zinc sulfate, zinc chloride, zinc bromide, magnesium bromide, copper chloride, copper sulfate, or any combination thereof. In an embodiment, the flocculant may be added to the mixture at a temperature below the glass transition temperature (Tg) of the resin.
[0073] The aggregating agent may be added to the mixture in an amount of, for example, from about 0.1 parts per million (pph) to about 1 pph, in embodiments from about 0.25 pph to about 0.75 pph, to form a toner.
[0074] The gloss of the toner is determined by the amount of Al in the toner particles. 3+ The amount of retained metal ions, such as Al, may be influenced by the amount of retained metal ions. The amount of retained metal ions may be further adjusted by the addition of ethylene diamine tetraacetic acid (EDTA). In embodiments, the amount of retained metal ions, such as Al, in the toner particles of the present disclosure may be adjusted by the addition of ethylene diamine tetraacetic acid (EDTA). 3+ The amount may be from about 0.1 pph to about 1 pph, in embodiments from about 0.25 pph to about 0.8 pph.
[0075] The present disclosure also provides a melt mixing process for producing low-cost, safe crosslinked thermoplastic binder resins for toner compositions that may have, for example, low fixation and / or high offset temperatures and minimized or substantially no vinyl offset. In this process, unsaturated polyesters, resins or polymers are melt blended, i.e., under high shear conditions, toner components are produced that are substantially uniformly dispersed in the molten state, and the process provides resin blends and toner products with optimized gloss properties (see, for example, U.S. Pat. No. 5,556,732, which is incorporated herein by reference in its entirety). "Highly crosslinked" means that the polymers involved are substantially crosslinked, i.e., at or above their gel point. As used herein, "gel point" means the point at which the polymer no longer dissolves in solution (see, for example, U.S. Pat. No. 4,457,998, which is incorporated herein by reference in its entirety).
[0076] To control particle aggregation and coalescence, in embodiments, the flocculant may be metered into the mixture over time. For example, the agent may be metered into the mixture over a period of from about 5 minutes to about 240 minutes, in embodiments from about 30 minutes to about 200 minutes. The addition of the agent may also be performed while maintaining the mixture under stirring conditions, in embodiments from about 50 rpm to about 1,000 rpm, in embodiments from about 100 rpm to about 500 rpm, and at 200° C. for 10 minutes. g This can be done while maintaining the temperature below
[0077] The particles may be aggregated until a predetermined desired particle size is obtained. The predetermined desired size refers to a desired particle size determined prior to formation, and the particle size is monitored during the growth process as known in the art until such particle size is achieved. Samples may be taken during the growth process and analyzed for average particle size, for example, with a Coulter Counter. Thus, aggregation may proceed by maintaining an elevated temperature or slowly increasing the temperature, for example, to about 40° C. to about 100° C., and holding the mixture at this temperature for a period of about 0.5 hours to about 6 hours, in embodiments about 1 hour to about 5 hours, while continuing to stir, to provide aggregated particles. Once the predetermined desired particle size is obtained, the growth process is stopped. In embodiments, the predetermined desired particle size is within the toner particle size range described above. In embodiments, the particle size may be about 5.0 to about 6.0 μm, about 6.0 to about 6.5 μm, about 6.5 to about 7.0 μm, or about 7.0 to about 7.5 μm.
[0078] The growth and shaping of the particles after addition of the agglomerating agent can be accomplished under any suitable conditions. For example, the growth and shaping can be carried out under conditions where agglomeration occurs separately from coalescence. For separate agglomeration and coalescence steps, the agglomeration process can be carried out at elevated temperatures, e.g., at temperatures above the T of the resin. g The curing may be carried out under shear conditions at temperatures of from about 40° C. to about 90° C., in embodiments from about 45° C. to about 80° C.
[0079] The toner may have good charging properties when exposed to extreme RH conditions. The low humidity zone (C-zone) may be about 12° C. / 15% RH, and the high humidity zone (A-zone) may be about 28° C. / 85% RH. The toner of the present disclosure may have a parent toner charge per mass ratio (Q / M) of about -5 μC / g to about -80 μC / g, in embodiments about -10 μC / g to about -70 μC / g, and a final toner charge after surface additive blending of -15 μC / g to about -60 μC / g, in embodiments -20 μC / g to about -55 μC / g. Shell Resin
[0080] In embodiments, a shell may be applied to the formed aggregate toner particles. Any of the resins described above suitable for the core resin may be utilized as the shell resin. The shell resin may be applied to the aggregate particles by any process within the purview of one skilled in the art. In embodiments, the shell resin may be present in an emulsion including any of the surfactants described herein. The aggregate particles may be combined with the emulsion such that the resin forms a shell on the formed aggregates. In embodiments, an amorphous polyester may be utilized to form a shell on the aggregates to form toner particles having a core-shell configuration.
[0081] The toner particles may have a diameter size of from about 4 to about 8 μm, in embodiments from about 5 μm to about 7 μm, and the optimal shell component may be from about 26% to about 30% by weight of the toner particle.
[0082] Alternatively, a thicker shell may be desirable to provide desirable charging characteristics due to the greater surface area of the toner particles. Thus, the shell resin may be present in an amount of from about 30% to about 40% by weight of the toner particles, in embodiments from about 32% to about 38% by weight of the toner particles, in embodiments from about 34% to about 36% by weight of the toner particles.
[0083] In embodiments, a photoinitiator may be included in the shell. Thus, the photoinitiator may be present in the core, the shell, or both. The photoinitiator may be present in an amount of from about 1% to about 5% by weight of the toner particles, in embodiments from about 2% to about 4% by weight of the toner particles.
[0084] The emulsions may have a solids loading of from about 5% to about 20% by weight solids, in embodiments from about 12% to about 17% by weight solids.
[0085] Once the desired final size of the toner particles is achieved, the pH of the mixture may be adjusted with a base (i.e., a pH adjuster) to a value of from about 6 to about 10, in embodiments from about 6.2 to about 7. The pH adjustment may be utilized to freeze to stop toner growth. The base utilized to stop toner growth may include any suitable base, such as an alkali metal hydroxide, such as sodium hydroxide, potassium hydroxide, ammonium hydroxide, or any combination thereof. In embodiments, EDTA may be added to assist in adjusting the pH to the desired value above. The base may be added in an amount of from about 2 to about 25% by weight of the mixture, in embodiments from about 4 to about 10% by weight of the mixture. In embodiments, the shell has a higher T than the aggregated toner particles. g has. Merge
[0086] Following aggregation to the desired particle size, the particles may be coalesced into the desired final shape, with optional formation of a shell as described above. Coalescing may be accomplished, for example, by heating the mixture to a temperature of about 55° C. to about 100° C., in embodiments from about 65° C. to about 75° C., which may be below the melting point of the crystalline resin to prevent plasticization. Higher or lower temperatures may be used, it being understood that the temperature is a function of the resin used.
[0087] Coalescence may proceed for about 0.1 hours to about 9 hours, in embodiments, for about 0.5 to about 4 hours.
[0088] After coalescence, the mixture may be cooled to room temperature, such as from about 20° C. to about 25° C. Cooling may be rapid or slow, as desired. A suitable cooling method may include introducing cold water into a jacket around the reactor. After cooling, the toner particles may optionally be washed with water and then dried. Drying may be accomplished by any suitable method, such as freeze drying. Career
[0089] A variety of suitable solid core or particle materials can be utilized for the carriers and developers of the present disclosure. Characteristic particle properties include, in embodiments, properties that allow the toner particles to acquire a positive or negative charge, and a carrier core that provides desirable flow properties in the developer reservoir present in an electrophotographic imaging device. Other desirable properties of the core include, for example, suitable magnetic properties to enable magnetic brush formation in the magnetic brush development process, desirable mechanical aging properties, and desirable surface morphology to enable high electrical conductivity of any developer containing the carrier and suitable toner.
[0090] Examples of carrier particles or cores that may be utilized include, but are not limited to, iron and / or steel, such as atomized iron or steel powder available from Hoeganaes Corporation or Pomaton SpA (Italy); ferrites, such as Cu / Zn-ferrite, containing about 11% copper oxide, about 19% zinc oxide, and about 70% iron oxide, available from DMSteward Corporation or Powdertech Corporation, Ni / Zn-ferrite available from Powdertech Corporation, Sr-ferrite, containing about 14% strontium oxide and about 86% iron oxide, and Ba-ferrite, available from Powdertech Corporation; magnetites, including those available from Hoeganaes Corporation (Sweden); nickel; and combinations thereof. In embodiments, the resulting polymer particles may be used to coat any known type of carrier core by various known methods, and the carriers are then incorporated with known toners to form developers for electrophotographic printing. Other suitable carriers are set forth, for example, in U.S. Patent Nos. 4,937,166, 4,935,326, and 7,014,971, the disclosures of each of which are incorporated herein by reference in their entirety, and may include granular zircon, granular silicon, glass, silicon dioxide, combinations thereof, and the like. In embodiments, suitable carrier cores may have, for example, an average particle size of from about 20 μm to about 400 μm in diameter, in embodiments from about 40 μm to about 200 μm in diameter.
[0091] In embodiments, ferrites may be utilized as the core and include a metal, such as iron, and at least one additional metal, such as copper, zinc, nickel, manganese, magnesium, calcium, lithium, strontium, zirconium, titanium, tantalum, bismuth, sodium, potassium, rubidium, cesium, strontium, barium, yttrium, lanthanum, hafnium, vanadium, niobium, aluminum, gallium, silicon, germanium, antimony, or any combination thereof.
[0092] In embodiments, a developer is disclosed that includes a resin coated carrier and a toner, which may be an emulsion aggregation toner that contains, but is not limited to, a latex resin, a wax, and / or a polymer shell. Conductive Components
[0093] In some embodiments, the carrier coating may include a conductive component. Suitable conductive components include, for example, carbon black.
[0094] The carrier may contain a number of additives, such as charge enhancing additives, such as certain particulate amine resins, such as melamine, and certain fluoropolymer powders, such as alkylaminoacrylates and methacrylates, polyamides, and fluorinated polymers, such as polyvinylidene fluoride and poly(tetrafluoroethylene), and fluoroalkyl methacrylates, such as 2,2,2-trifluoroethyl methacrylate. Other charge enhancing additives that may be utilized include quaternary ammonium salts, such as distearyl dimethyl ammonium methyl sulfate (DDAMS), bis[1-[(3,5-disubstituted-2-hydroxyphenytoyl)-3-(monosubstituted)-2-naphthalenolate(2-)]chromate(1-), ammonium sodium and hydrogen (TRH), cetyl pyridinium chloride, and the like. chloride, CPC), FANALPINK® D4830, or any combination thereof, and / or other effective known charge agents or additives. The charge additive component may be selected in various effective amounts, such as, for example, from about 0.5% to about 20% by weight, from about 1% to about 3% by weight, based on the total weight of the polymer / copolymer, conductive component, and other charge additive components. The addition of the conductive component can act to further increase the negative triboelectric charge imparted to the carrier and thus, for example, toner in an electrophotographic development subsystem. The components can be incorporated by roll mixing, tumbling, milling, shaking, electrostatic powder cloud spraying, fluidized bed, electrostatic disk processing, and electrostatic curtain, as described, for example, in U.S. Pat. No. 6,042,981, the disclosure of which is incorporated herein by reference in its entirety, and the carrier coating is fused to the carrier core in a rotary kiln or by passing through a heated extruder apparatus.
[0095] Conductivity can be important for semiconductive magnetic brush development, which allows for good development of solid areas that may otherwise be poorly developed. The addition of the polymer coating of the present disclosure, optionally with a conductive component such as carbon black, can result in a carrier in which the triboelectric response of the developer decreases with a change in relative humidity of about 20% to about 90%, in embodiments about 40% to about 80%, and the charge is more stable as the relative humidity changes. Thus, there is less charge loss at high relative humidity, which reduces background toner on the print, and less charge increase at low relative humidity, which subsequently results in less development loss, resulting in improved optical density, which results in such improved image quality performance.
[0096] As mentioned above, in embodiments, the polymer coating may be dried and then applied to the core carrier as a dry powder. The powder coating process differs from the conventional solution coating process. Solution coating requires a coating polymer whose composition and molecular weight characteristics allow the resin to be soluble in the solvent during the coating process. Solution coating has a relatively low M compared to powder coating. w Powder coating processes do not require solvent solubility, but rather require the resin to be coated as fine particles having a particle size of from about 10 nm to about 2 μm, in embodiments from about 30 nm to about 1 μm, and in embodiments from about 50 nm to about 500 nm.
[0097] Examples of processes that can be utilized to apply powder coatings include combining a carrier core material with a resin coating, for example, by cascade roll mixing, tumbling, milling, shaking, electrostatic powder cloud spraying, fluidized bed, electrostatic disk processing, electrostatic curtain, combinations thereof, and the like. When resin-coated carrier particles are prepared by a powder coating process, a majority of the coating material can be fused to the carrier surface, thereby reducing the number of toner impaction sites on the carrier. Fusing of the polymer coating can occur by mechanical adhesion, electrostatic attraction, or a combination thereof, and the like.
[0098] After the resin is applied to the core, heating can be initiated to cause the coating material to flow onto the surface of the carrier core. The concentration of coating material, in embodiments, powder particles, and heating parameters can be selected to allow the formation of a continuous film of coating polymer on the surface of the carrier core, or to allow only selected areas of the carrier core to be coated. In embodiments, the carrier with the polymer powder coating can be heated to a temperature of about 170° C. to about 280° C., in embodiments, 190° C. to 240° C., for a period of time, for example, about 10 minutes to about 180 minutes, in embodiments, about 15 minutes to about 60 minutes, to melt and fuse the polymer coating to the carrier core particles. After incorporating the powder on the surface of the carrier, heating can be initiated to cause the coating material to flow onto the surface of the carrier core. In embodiments, the powder can be fused to the carrier core in a rotary kiln or by passing through a heated extruder apparatus, as described, for example, in U.S. Pat. No. 6,355,391, the disclosure of which is incorporated herein by reference in its entirety.
[0099] In embodiments, the coating coverage encompasses from about 10% to about 100% of the carrier core. When selected areas of the metal carrier core are left uncoated or exposed, the carrier particles may have conductive properties when the core material is metallic.
[0100] The coated carrier particles may then, in embodiments, be cooled to room temperature and recovered for use in forming the developer.
[0101] In embodiments, the carrier of the present disclosure may comprise a ferrite core having a size, in embodiments, of from about 20 μm to about 100 μm, in embodiments, from about 30 μm to about 75 μm, coated with from about 0.5% to about 10% by weight, in embodiments, from about 0.7% to about 5% by weight of a polymer coating of the present disclosure, optionally including carbon black.
[0102] Thus, with the carrier compositions and processes of the present disclosure, a number of different combinations can be utilized to formulate developers having selected high triboelectric charging properties and / or conductivity values. Developer
[0103] The toner particles thus formed may be formulated into a developer composition. The toner particles may be mixed with carrier particles to obtain a two-component developer composition. The toner concentration in the developer may be from about 1% to about 25% by weight of the total weight of the developer, in embodiments from about 2% to about 15% by weight of the total weight of the developer. Imaging
[0104] Toners may be utilized in electrophotographic processes, including those disclosed in U.S. Patent No. 4,295,990, the disclosure of which is incorporated herein by reference in its entirety. In embodiments, any known type of development system may be used in the image development device, including, for example, magnetic brush development, hybrid scavengeless development (HSD), and the like. These and similar development systems are within the purview of those skilled in the art.
[0105] It is contemplated that the toners of the present disclosure may be used in any suitable procedure for forming images with toner, including applications other than xerographic applications.
[0106] Utilizing toners of the present disclosure, images may be formed on substrates, including flexible substrates, having a toner pile height of from about 1 μm to about 6 μm, in embodiments from about 2 μm to about 4.5 μm, and in embodiments from about 2.5 μm to about 4.2 μm.
[0107] In embodiments, the toners of the present disclosure may be used for xerographic print protection compositions that provide overprint coating properties, including but not limited to heat and light stability, and smear resistance, particularly in commercial printing applications. More specifically, such overprint coatings as envisioned have the ability to allow overprinting, reduce or prevent thermal degradation, improve fusing, reduce or prevent document offset, improve print performance, and protect images from sun, heat, and the like. In embodiments, the overprint composition may be used to improve the overall appearance of the xerographic print due to the composition's ability to fill in the roughness of the xerographic substrate and toner, thereby forming a flat film and increasing gloss.
[0108] The following examples are presented to illustrate the embodiments of the present disclosure. These examples are intended to be illustrative only and are not intended to limit the scope of the present disclosure. Also, unless otherwise stated, parts and percentages are by weight. Comparative examples and data are also provided. EXAMPLES
[0109] The following examples are presented to further define the various species of the present disclosure. These examples are intended to be illustrative only and are not intended to limit the scope of the present disclosure. Also, unless otherwise stated, parts and percentages are by weight.
[0110] 5 grams of silica gel powder (SiO 2 Sigma Aldrich 236772) in 3 mL of silicon tetrachloride (SiCl 4) to form a dispersion. To this dispersion was added 2 grams of ZnCCA (BONTRON E-108™ phenol zinc organometallic) solution in tetrahydrofuran, and the mixture was stirred at room temperature for several hours. 4.5 grams of the filtered and dried powder was mixed with 45 grams of SrTiO 3 and thoroughly ground using a mortar and pestle.
[0111] SiO as described in Example 1 2 / SiCl 4 / Zn CCA-treated SrTiO 3 were blended at 0.2 pph and 0.4 pph and blended with cyan toner particles in a 10 liter blender for 10 minutes at 3000 rpm along with a standard toner additive package including titania, small / medium silica, large colloidal silica, and zinc stearate.
[0112] Triboelectric performance criteria: A significant effect should be observed in most dry environments and preferably absent in wet conditions.
[0113] SiCl bonded to Zn charge control agent 4 0.2 pph and 0.4 pph SrTiO 3 was blended with cyan toner particles in a 10 liter blender at 3000 rpm for 10 minutes along with a standard additive package including titania, small / medium silica, large colloidal silica, and zinc stearate.
[0114] The triboelectric properties of the resulting toner blends were measured under various humidity conditions: nominal (70°F (21°C) / 50% RH), dry (70°F (21°C) / 10% RH), and humid (80°F (27°C) / 80% RH) and are shown in Figure 1. 2 / SiCl 4 / Zn CCA-treated SrTiO 3 Toners made with the SiO 2 / SiCl 4 / Zn CCA-treated SrTiO 3was comparable to the control sample. The humid environment effect was greater than expected. Based on the dry / nominal results, SiCl bound to the Zn CCA 4 SrTiO 3 was reexamined at a higher concentration. In a dry environment, SiO 2 / SiCl 4 / ZnCCA-treated SrTiO 3 shows slightly lower charging, and SiO 2 / SiCl 4 / ZnCCA-treated SrTiO 3 This suggests that the charge could be adjusted by changing the concentration of
[0115] SiO at 50% of typical titania loading and 100% of typical titania loading 2 / SiCl 4 / Zn CCA-treated SrTiO 3 was blended with cyan toner particles along with a standard additive package containing small / medium silica, large colloidal silica, and zinc stearate. No titania was present in these blends. As shown in Figure 2, in a humid environment, SiO 2 / SiCl 4 / ZnCCA-treated SrTiO 3 The SiO2 at 50% and 100% titania loading had lower charging than the titania-containing control. 2 / SiCl 4 / ZnCCA-treated SrTiO 3 The charging was slightly higher than that of the titanium-containing control. In a dry environment, the SiO 2 / SiCl 4 / ZnCCA-treated SrTiO 3 had lower charging than the titania-containing SrTiO3 control. Figure 3A shows the resulting charging spectrum of the control.
[0116] 3B and 3C show SiO at 0.65 and 1.1 pph. 2 / SiCl 4 / ZnCCA-treated SrTiO3 Charging spectrum results for toner blends are shown. Charging spectra were obtained at 0, 15 seconds, 30 seconds, and 1 minute of toner addition. The "bell curve" shows the distribution of triboelectric charge. It is desirable for the "bell curve" to change as little as possible with the addition of toner at various times. When evaluating a new toner blend additive, it is further desirable for its charging characteristics with the toner addition to be as similar as possible to that of the control material. SiO 2 / SiCl 4 / ZnCCA-treated SrTiO 3 The charging spectrum behavior of the toner with the toner is very similar to that of the control material.
[0117] It will be appreciated that the various embodiments of the various above-disclosed and other features and functions, or alternatives thereof, may be desirably combined into many other different systems or applications. Also, various presently unanticipated or unprecedented alternatives, modifications, variations, or improvements may occur to those skilled in the art, which are also intended to be encompassed by the following "claims." Unless specifically recited in the claims, no particular order, number, position, size, shape, angle, color, or material of the steps or components of the claims should be implied or implied from this specification or any other claim.
Claims
1. 1. A toner composition comprising:
1. A toner particle comprising: toner particles comprising a resin; A colorant; A surface additive applied to the surface of the toner particles, the surface additive being strontium titanate (SrTiO 3 ), silica (SiO 2 ), silicon tetrachloride (SiCl 4 ) and a surface additive comprising a metal charge control agent.
2. The toner composition of claim 1 further comprising a wax.
3. The toner composition of claim 1 further comprising a coagulant.
4. The toner composition of claim 1 further comprising a flow additive.
5. 2. The toner composition of claim 1, wherein said surface additive is present in an amount of from about 0.2 parts per million (pph) to about 1.1 pph based on the total weight of said toner composition.
6. The toner composition of claim 1 further comprising a surfactant.
7. The metal charge control agent is a compound selected from the group consisting of zinc, aluminum, chromium, calcium and iron. The toner composition of claim 1 comprising a metal selected from:
8. 2. The toner composition of claim 1, wherein said metallic charge control agent comprises 3,5-di-tert-butylsalicylic acid zinc salt.
9. A developer comprising:
1. A toner composition comprising: Toner particles; A colorant; A surface additive applied to the surface of the toner particles, the surface additive being strontium titanate (SrTiO 3 ), silica (SiO 2 ), silicon tetrachloride (SiCl 4 ) and a surface additive comprising a metal charge control agent; and The developer includes a toner carrier.
10. 10. The developer of claim 9, wherein the toner composition is an emulsion aggregation toner composition.
11. 10. The developer of claim 9, wherein the surface additive is present in an amount of from about 0.2 parts per million (pph) to about 1.1 pph based on the total weight of the toner composition.
12. 1. A toner composition comprising:
1. A toner particle comprising: toner particles comprising a resin; A surface additive applied to the surface of the toner particles, the surface additive being strontium titanate (SrTiO 3 ), silica (SiO 2 ), silicon tetrachloride (SiCl 4 ) and a surface additive comprising a metal charge control agent.
13. The toner composition of claim 12 further comprising a wax.
14. The toner composition of claim 12 further comprising a coagulant.
15. 13. The toner composition of claim 12, wherein said metallic charge control agent comprises 3,5-di-tert-butylsalicylic acid zinc salt.
16. The toner composition of claim 12 further comprising a flow additive.
17. The toner composition of claim 12, wherein said surface additive is present in an amount from about 0.2 parts per million (pph) to about 1.1 pph based on the total weight of said toner composition.
18. The toner composition of claim 12 further comprising a surfactant.
19. 13. The toner composition of claim 12, wherein said metallic charge control agent comprises a metal selected from the group consisting of zinc, aluminum, calcium, chromium and iron.
Citation Information
Patent Citations
Toner
JP2015028601A